The thirteenth step : addiction in the age of brain science - Heilig, Markus (New York : Columbia University Press, 2015)
"The past twenty-five years have witnessed a revolution in the science of addiction, yet we still rely upon sorely outdated methods of treatment. Expensive new programs for managing addiction are also flourishing, but since they are not based in science, they offer little benefit to people who cannot afford to lose money or faith in their recovery. Clarifying the cutting-edge science of addiction for practitioners and general readers, The Thirteenth Step pairs stories of real patients with explanations of key concepts relating to their illness. A police chief who disappears on the job illustrates the process through which a drug can trigger the brain circuits mediating relapse. One person's effort to find a burrito shack in a foreign city illuminates the reward prediction error signaled by the brain chemical dopamine. With these examples and more, this volume paints a vivid, relatable portrait of drug seeking, escalation, and other aspects of addiction and suggests science-based treatments that promise to improve troubling relapse rates. Merging science and human experience, The Thirteenth Step offers compassionate, valuable answers to anyone who hopes for a better handle on a pernicious and confounding disease."--Publisher description.
Us and them -- A grocery store that closed -- An entity in its own right -- A chronic, relapsing disorder -- Man or machine? -- Histories, brains, and behaviors -- The pursuit of happiness -- The dark side of addiction -- Rash actions -- Turning on a red light -- Getting the cue -- A strained mind -- Fathers and sons -- Molecular culprits -- Trick or treatment -- Please behave -- Pills for addiction ills -- Pray if you wish, but please take your meds first -- The journey ahead.
Includes bibliographical references and index.
Keywords: Substance abuse -- Physiological aspects; Substance abuse -- Treatment; Substance abuse -- Physiological aspects; Substance abuse -- Treatment